Protocols and safety measurements used in intubation of COVID-19 patients - Bogari, Ahmed Fouad; Alharbi, Nada Mohmmad; Alaqlan, Mohammed Abdulrahman; Aljaza, Turki Salem; Alibrahim, Ali Ibrahim; Ali, Fadwa Ahmed; Alduhayshi, Ibrahim Saad; Ghandoora, Yasmeen Marwan; Alhajeri, Majed Nasser; Alshehri, Abdullah Yahya; Alqahtani, Naif Hussain (International Journal Of Community Medicine And Public Health, 2022)
The COVID-19 pandemic has forced many countries to pose an emergency to contain the contamination and prevent the further spread of the infection. In this context, many societies and research papers were published to optimize guidelines and protocols for patients undergoing surgery and subsequent intubation. Accordingly, infection control is a critical approach to reduce the rate of contamination and risk of catching infections for suspected and confirmed COVID-19 patients. As a result, various guidelines were discussed in the current literature review, including guidelines to the patient, healthcare workers, operating room, anesthesia equipment, and patient transportation. For instance, healthcare workers can protect themselves from catching infections by wearing personal protective equipment and conducting adequate disinfection measures following each operation, in addition to the proper disposal of the contaminated objects. Strictly following these protocols should be done to reduce the risk of contamination in the operating room and enhance the outcomes of the patients and healthcare workers.